2021
DOI: 10.3390/polym13081340
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Stimuli-Responsive In Situ Gel System for Sustained Ocular Drug Delivery: Recent Progress and Contemporary Research

Abstract: Eyesight is one of the most well-deserved blessings, amid all the five senses in the human body. It captures the raw signals from the outside world to create detailed visual images, granting the ability to witness and gain knowledge about the world. Eyes are exposed directly to the external environment; they are susceptible to the vicissitudes of diseases. The World Health Organization has predicted that the number of individuals affected by eye diseases will rise enormously in the next decades. However, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 107 publications
(235 reference statements)
0
13
0
Order By: Relevance
“…From the obtained data, it was concluded that the relative bioavailability of the BH-loaded in situ gel was higher than the drug solution by more than 1.5-fold. The enhanced relative bioavailability of the BH may have been due to the decreased release of the drug from the in situ gel, which led to a more sustained release and absorption of the drug compared to the free-solution form [ 15 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the obtained data, it was concluded that the relative bioavailability of the BH-loaded in situ gel was higher than the drug solution by more than 1.5-fold. The enhanced relative bioavailability of the BH may have been due to the decreased release of the drug from the in situ gel, which led to a more sustained release and absorption of the drug compared to the free-solution form [ 15 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gels are semisolid dosage forms with three-dimensional polymeric matrices comprising a small amount of solids carrying a large amount of liquid ( Pandey et al, 2021 ). The in situ gelling system has the capability to convert from sol-to-gel upon application to the site of administration.…”
Section: Recent Advancement Of Delivering Antipsychotics Using Intran...mentioning
confidence: 99%
“…These polymers cause a slower elimination of the drug; examples are cellulose derivatives such as protein (collagen, silk, gelatin), polysaccharide (chitosan, starch, alginate), polyesters (polycaprolactone, polylactide, polylactide/polyglycolic copolymer) [35], and cellulose derivatives such as HPMC [77], hydroxyethyl cellulose [78], and methylcellulose. In situ gels are delivered as a solution or suspension and rapidly undergoes sol-gel transition [79] upon external stimuli such pH, temperature, and ionic strength [80]. This has merits such as reproducible and accurate dosing.…”
Section: Strategies For Enhancing Ocular Drug Delivery Systemmentioning
confidence: 99%